Visual–vestibular sensory integration during congruent and incongruent self-rotation percepts using caloric vestibular stimulation - Kirollos, Ramy; Herdman, Chris M. (Frontiers in Virtual Reality, 2023)
The present study sets out to determine which sensory system most influences selfmotion perception when visual and vestibular cues are in conflict. We paired caloric vestibular stimulation that signaled motion in either the clockwise or counter-clockwise direction with a visual display that indicated self-rotation in either the same or opposite directions. Method: In Experiment 1 (E1), caloric vestibular stimulation was used to produce vestibular circular vection. In Experiment 2 (E2), a virtual optokinetic drum was used to produce visual circular vection in a VR headset. Vection speed, direction and duration were recorded by a potentiometer knob the participant controlled in E1 and E2. In Experiment 3 (E3), visual and vestibular stimuli were matched to be at approximately equal speeds across visual and vestibular modalities for each participant setting up Experiment 4 (E4). In E4, participants observed a moving visual pattern in a VR headset while receiving caloric vestibular stimulation. Participants rotated the potentiometer knob while attending to visual-vestibular stimuli presentations to indicate their perceived circular vection. E4 had two conditions: 1) A congruent condition where calorics and visual display indicated circular vection in the same direction. 2) An incongruent condition where calorics and visual display indicated circular vection in opposite directions. Results and Discussion: There were equal reports of knob rotation in the direction consistent with visual and vestibular self-rotation direction in the incongruent condition of E4 across trials. There were no significant differences in knob rotation speed and duration in both conditions. These results demonstrate that the brain appears to weigh visual and vestibular cues equally during visual-vestibular conflict of approximately equal speeds. These results are most consistent with optimal cue integration hypothesis.